Akame ga kill!. Vol. 1 - Takahiro, 1981- (Yen Press, 2015)
Teenage country bumpkin Tatsumi dreams of earning enough money for his impoverished village by working in the Capital--but his short-lived plans go awry when he's robbed by a buxom beauty upon arrival! Penniless, Tatsumi is taken in by lovely Miss Aria, but just when his Capital dreams seem in reach yet again, Miss Ara's mansion is beseiged by Night Raid -- a team of ruthless assassins who target high-ranking members of the upper class! As Tatsumi is quick to learn, appearances can be deceiving in the Capital, and this team of assassins just might be...the good guys?!